2020
DOI: 10.2147/jpr.s259390
|View full text |Cite
|
Sign up to set email alerts
|

<p>Acupuncture versus Various Control Treatments in the Treatment of Migraine: A Review of Randomized Controlled Trials from the Past 10 Years</p>

Abstract: Background: Migraine is defined as a recurrent headache of moderate to severe intensity that seriously affects the quality of life. Recent clinical trials have confirmed that acupuncture is effective in treating migraine. We aimed to review the effectiveness of acupuncture in the treatment of migraine by comparing treatment and various control groups in accordance with the newly published guidelines for systematic reviews. Materials and Methods: The following databases were searched for relevant articles publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
5
0
3
Order By: Relevance
“…Where migraine and headache carry a significant global economic burden [ 100 ], real-world data from a 10-year national cohort study in Taiwan showed that in patients with migraine who received acupuncture treatment, medical expenditures on emergency care and hospitalization were significantly lower than those of the group without acupuncture treatment [ 80 ]. A review of 10 years of RCTs of acupuncture vs various controls in the treatment of migraine (49 trials) found that acupuncture reduces symptoms of migraine and improves quality of life [ 101 ]. The meta-analysis showed that acupuncture reduces headache frequency more than no treatment or medications, but the quality of evidence was low.…”
Section: Resultsmentioning
confidence: 99%
“…Where migraine and headache carry a significant global economic burden [ 100 ], real-world data from a 10-year national cohort study in Taiwan showed that in patients with migraine who received acupuncture treatment, medical expenditures on emergency care and hospitalization were significantly lower than those of the group without acupuncture treatment [ 80 ]. A review of 10 years of RCTs of acupuncture vs various controls in the treatment of migraine (49 trials) found that acupuncture reduces symptoms of migraine and improves quality of life [ 101 ]. The meta-analysis showed that acupuncture reduces headache frequency more than no treatment or medications, but the quality of evidence was low.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the frequency of acupuncture seems challenging to quantify. Although the analgesic effect of the acupuncture group was superior to the control groups, it cannot be neglected that on the management of some pain (pain in labor, migraine, and neuropathic pain), low-quality evidence suggests that acupuncture does not differ much from usual care [41][42][43]. Since a large number of the current RCTs provide conflicting and inconclusive evidence, the methodological shortcomings of RCTs are recurrent [43,44].…”
Section: Clinical Research Condition Of Acupuncture Analgesiamentioning
confidence: 97%
“…Хотя данные специальных исследований влияния различных методов физической активности лимитированы ограниченным количеством работ и отсутствием адекватного контроля, тем не менее в отношении аэробных упражнений можно сделать несколько практических выводов [48] И г л о р е ф л е к с о т е р а п и я В качестве важного компонента КАМ рефлексотерапия приобрела популярность как метод паллиативного вмешательства [55]. Клинические исследования показали, что ИРТ может уменьшать интенсивность боли, ее продолжительность, влиять на эмоциональную сопутствующую патологию и количество препаратов, принимаемых для купирования болевых эпизодов.…”
Section: Characteristics Of Lifestyle Changes To Overcome the Negativ...unclassified
“…С развитием биомедицинских и нейровизуализационных методов все большее внимание привлекают нейрогенные механизмы ИРТ при мигрени. Нейровизуализационные исследования показали, что ИРТ может изменить аномальную функциональную активность системы модуляции нисходящей боли, таламуса, лобно-теменной, затылочновисочной областей и мозжечка, уменьшать нейровоспаление, регулировать периферическую и центральную сенситизацию [55].…”
Section: Characteristics Of Lifestyle Changes To Overcome the Negativ...unclassified